Synchrotron radiation FTIR microspectroscopy enables measuring dynamic cell identity patterning during human 3D differentiation - Dučić, Tanja; Rodriguez-Yañez, Francisco; Gonzalez-Muñoz, Elena (Frontiers in Cell and Developmental Biology, 2025)
Human cell fate specification, particularly in neural development, is difficult to study due to limited access to embryonic tissues and differences from animal models. Human induced pluripotent stem cells (hiPSCs) and 3D organoid models enable the study of early human neural development, surpassing limitations of 2D cultures by incorporating crucial cell-cell and cell-matrix interactions. In this study, we used synchrotron radiation-based Fourier transform infrared (SR-FTIR) microspectroscopy to examine biomolecular profiles of 3D-differentiated organoids, specifically embryoid bodies (EBs) and neural spheroids (NS), derived from hiPSCs. SR-FTIR allowed us to analyze these organoids’ cellular identity at a biomolecular level, offering a holistic view that complements specific cell markers. Our findings reveal distinct biomolecular identities in 3D organoids, with differences in DNA structure, lipid saturation, phospholipid composition, and protein conformations. This approach highlights that cellular identity is shaped by more than gene expression alone; it involves unique biomolecular compositions that can be detected even in complex, multicellular environments. By demonstrating the role of molecular configuration in cell differentiation, our findings suggest that differentiation processes extend beyond genetics, involving interdependent biochemical signals. This study demonstrates the unique efficacy SR-FTIR in analyzing human-specific 3D models for investigating complex multicellular differentiation mechanisms, offering new avenues for understanding the biochemical basis of human development and disease.